GELIAT PERTENTANGAN FUNDAMENTALISME DAN LIBERALISME - Evi Sopandi (Jurnal Dialog, 2017)
The article discusses the weaknesses of Fundamental and Liberal Muslims. The weakness of Liberal Muslims is placed on their superficial thinking. When they are reluctant to embody the Law of God, their reluctance is polished with their jargon--back to the spirit of the Koran are human and fair. It seems that they, then, remove the Lord’s ordinances, which actually have a certain positive value. They ran from God and made up the rule of law based on the creativity of a mind or their free logical thinking. Meanwhile, the fundamentalists’ weakness is their low tolerance of various differences of religious thoughts. Therefore, sometimes they are easy to claim that the differences are apostasy and unbelief, without dialogue. To get a broader outlook of both this article examines the two poles of thoughts.